Smart materials and martensite microstructures in copper based shape memory alloys - Adiguzel, O. (Springer, 2006)
One particular group of materials exhibits a peculiar property called shape memory effect. Metastable beta-phases of ternary alloys based on the noble metal copper have basically a bee structure but homogenize as B2(CsCl) or DO3 (Fe3Al) type ordered structures at high temperatures, and martensitically transform to layered structures, such as 3R, 9R or 18R, depending on the stacking sequences of the {110} - type planes of the parent phase.
Conference of the NATO-Advanced-Study-Institute on Functional Properties of Nanostructured Materials -- JUN 03-15, 2005 -- Sozopol, BULGARIA
Keywords: shape memory alloys; martensite; layered structures; hexagonal distortion